Valorisation of animal and plant biomass into wound dressings - Lau, Huan Yi (Nanyang Technological University, 2023)
Despite medical advances in acute trauma care, haemorrhage after injury contributes to over half of the five million traumatic deaths that occur every year. As such, this has placed a huge burden in the healthcare sector. Effective control of hemorrhage will lead to dramatic reductions in pre-hospital and in-hospital mortality. Even though there are many hemostatic agents available in the market, they still face problems with biocompatibility and processing. Individually, collagen and cellulose have excellent biocompatibility and biological properties, but their combined hemostatic property has not been fully explored. Collagen generally exhibits poor mechanical and physical properties that limits its potential applications in its native form, hence the incorporation of cellulose aims to overcome these problems. Cellulose in the form of cellulose nanofibrils (CNFs) exhibit tunable surface chemistry, easy functionality and high aspect ratio nanostructures, making it a suitable candidate as reinforcement material. In this study, cellulose nanofibrils (CNFs) were extracted from various sources of cellulose via TEMPO-mediated oxidation prior to incorporation with bullfrog collagen to make a nanocomposite sponge as a sustainable hemostatic dressing. Formulation variables included material mass, sources of cellulose, and types of crosslinker were explored targeted to develop a nanocomposite wound dressing with good structural integrity and high water uptake.Cytocompatibility testing showed favourable attachment and spreading of viable Human Dermal Fibroblast (HDF) cells seeded on the nanocomposite sponge as confirmed by live-dead assay. Overall, exploring this strategy of preparing hemostatic dressings through valorisation for prehospital phase of wound care can help to reduce waste and work towards a circular bioeconomy.